Evolution of welding residual stresses involving the cutting process and its effect on fatigue performance. (June 2022) - Zhan, Rui; Wang, Dongpo; Ren, Zhiguo; Deng, Caiyan; Xu, Xiaohan; Liang, Hang
Abstract: In this study, the residual stress distributions in welded joints with different widths with or without the mechanical cutting process were simulated, and the relevant effects on fatigue performance were focused. The stress intensity factor ( K ) for the welded joints with different widths was evaluated using the membrane/bending components of corresponding transverse residual stress as the fracture-driving force. The results revealed that residual stress relaxation occurred when the welded joint was cut, which further reduced the effect of residual stresses on fatigue performance. Meanwhile, there existed a significant size effect on the residual stress distribution for the welded joints without the cutting process. The width-to-thickness ratio for welded joints can be parameterized in terms of the degree of residual stress retention. The value of K could decrease significantly when the width-to-thickness ratio of the welded joint after the cutting process was less than 10. However, the K value for the welded joints without the cutting process could not be enhanced by increasing the width-to-thickness value. The degree of retention for welding residual stresses must be considered in the laboratory tests if the welded joint is cut. Furthermore, the effects of residual stresses can be fully considered using an as-welded (AW) joint with a width-to-thickness ratio of approximately ten, according to this study. Highlights: The size effect on the residual stress distributions in the welded joint was concerned. The welding residual stress relaxations caused by the cutting process were obtained. The effects of welding residual stress on fatigue performance were assessed based on fracture mechanics. Mechanisms on the residual stress relaxation caused by the cutting process were analyzed. Mechanisms on the formation of welding residual stress in different wide joints were discussed.